2020
DOI: 10.1002/jcpy.1195
|View full text |Cite
|
Sign up to set email alerts
|

When Sustainability is Not a Liability: The Halo Effect of Marketplace Morality

Abstract: Prior research has suggested that consumers believe that products made using sustainable, environmentally friendly technologies are likely to underperform those made using traditional methods. We question the robustness of this assumption and identify scenarios in which sustainability is likely to have the opposite effect, strengthening rather than weakening consumers' product performance beliefs. Specifically, we argue that sustainability is likely to produce a halo effect able to attenuate and even override … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 43 publications
(62 reference statements)
6
26
0
Order By: Relevance
“…Moreover, hypothesis 3 found a significant relationship between campaign evaluations and company evaluations. In line with previous studies [13,[20][21][22][23][24], this study adds to the findings that social distance perception from a company may hinder fair consumer evaluations and that social distance mitigation can help foreign firms overcome negative consumer evaluations and the costs of LOF.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, hypothesis 3 found a significant relationship between campaign evaluations and company evaluations. In line with previous studies [13,[20][21][22][23][24], this study adds to the findings that social distance perception from a company may hinder fair consumer evaluations and that social distance mitigation can help foreign firms overcome negative consumer evaluations and the costs of LOF.…”
Section: Discussionsupporting
confidence: 88%
“…The association between CSR campaign evaluations and consumer evaluations such as corporate image and purchase intentions has been found in a considerable number of studies [13,[20][21][22][23][24]. Through sustainability activities, foreign firms can persuade local consumers that they are beneficial to society and help align their values and beliefs with local consumers.…”
Section: The Mediating Role Of Sustainability Campaign Initiatives Bementioning
confidence: 99%
“…However, in their recent study, Chernev and Blair [21] found new evidence for limits of the sustainability liability. They documented the effect on perceived product performance for consumers with weak environmental values only, and showed "that for sustainabilityconscious respondents, whose moral beliefs were aligned with preserving the environment, the presence of sustainable benefits bolstered perceived product performance" (p. 9).…”
Section: The Sustainability Liability In Performance Perceptionmentioning
confidence: 99%
“…Prior research has studied consumers' perceptions of products that used sustainable vs. traditional technologies (for an overview, see Chernev and Blair [21]). Studies have consistently documented that sustainability does not necessarily raise preferences, even if consumers care about social and environmental issues, but actually decrease preferences.…”
Section: The Sustainability Liability In Performance Perceptionmentioning
confidence: 99%
See 1 more Smart Citation